Extracellular Vesicles in Liver Pathobiology: Small Particles with Big Impact - Hirsova, Petra (Hepatology, 2016)
Extracellular vesicles (EVs) are nanometer-sized, membrane-bound vesicles released by cells into the extracellular milieu. EVs are now recognized to play a critical role in cell-to-cell communication. EVs contain important cargo in the form of proteins, lipids and nucleic acids and serve as vectors for delivering this cargo from donor to acceptor or target cell. The EVs are released both under physiologic and pathologic conditions, including liver diseases, and exert a wide range of effects on target cells. This review provides an overview on EV biogenesis, secretion, cargo, and target cell interactions in the context of select liver diseases. Specifically, the diverse roles of EVs in nonalcoholic steatohepatitis, alcoholic liver disease, viral hepatitis, cholangiopathies and hepatobiliary malignancies are emphasized. Liver diseases often result in an increased release of EVs and/or in different cargo sorting into these EVs. Either of these alterations can drive disease pathogenesis. Given this fact, EVs represent a potential target for therapeutic intervention in liver disorders. Because altered EV composition may reflect the underlying disease condition, circulating EVs can be exploited for diagnostic and prognostic purposes as a liquid biopsy. Furthermore, ex vivo modified or synthesized EVs can be engineered as therapeutic nano-shuttles. Finally, we highlight areas that merit further investigation relevant to understanding how EVs regulate liver disease pathogenesis.